Use of dental management software to improve administrative efficiency in clinics in the city of Cuenca (Research, Society and Development, 2025)
Introduction: Currently, the digital transformation in the healthcare sector has driven the use of specialized software to optimize administrative processes, as in the case of dental clinics, improving service quality and operational efficiency. Objective: This study seeks to analyze the impact of using dental management software on the administrative efficiency of clinics in the city of Cuenca, with an emphasis on benefits, challenges, and personal perceptions. Materials and methods: A descriptive and comparative methodological approach was used, based on a literature review and the administration of a structured questionnaire to faculty and administrative staff at the Faculty of Dentistry of the University of Cuenca. This allowed for comparing real-life user experiences with theoretical challenges. Results: The studies revealed that, although the current system is widely used for various administrative tasks, it has limitations in terms of functionality and user capacity, which impact its efficiency. In contrast, specialized platforms such as Dentalink and Doctoqlic have gained popularity and are presented as more comprehensive and easy-to-use tools, although their adoption can face barriers in terms of cost and resistance to system change. Conclusion: The implementation of specialized software in the dental sector, accompanied by appropriate technical training, can significantly improve administrative efficiency and contribute to more organized, agile, and patient-centered dental care.